2008
DOI: 10.1007/s00066-008-1867-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Levels during the Course of Radiotherapy

Abstract: A preexisting selenium deficiency could be diagnosed in the broad majority of cancer patients undergoing radiotherapy. In contrast to the widely held opinion, it was not further aggravated by standard radiotherapy protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…There is also an ongoing debate whether low serum selenium levels after radiation therapy are indeed the result of radiation injury or if they are a consequence of prior chemotherapy, pre-existing nutritional deficiencies, or the presence of a tumor (18–20). Our study clearly shows that TBI (in the absence of a tumor, pre-existing nutritional deficiencies, or prior chemotherapy) is sufficient to cause a long-lasting reduction of serum selenium levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an ongoing debate whether low serum selenium levels after radiation therapy are indeed the result of radiation injury or if they are a consequence of prior chemotherapy, pre-existing nutritional deficiencies, or the presence of a tumor (18–20). Our study clearly shows that TBI (in the absence of a tumor, pre-existing nutritional deficiencies, or prior chemotherapy) is sufficient to cause a long-lasting reduction of serum selenium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that RT is able to change the status of the antioxidant/oxidant system, [23][24][25][26][27] while other reports have pointed out this treatment does not have big effects on the antioxidant/oxidant system. 23,28,29 Therefore, in this study, we aimed to determine the exact effects of RT on the oxidant/antioxidant status, the activity of glutathione peroxidase (GPx) and the levels of catalase (CAT), superoxide dismutase (SOD) and selenium (Se) in a group of women with breast cancer. To this end, we followed all the patients before and after RT to determine the effects of this type of treatment on aforementioned variables.…”
Section: Aimmentioning
confidence: 99%
“…Selenium deficiency is nearly the norm in cancer patients [ 38 , 39 ]. Radio- and chemotherapy as well as the suboptimal nutrition of cancer patients in the clinics might aggravate the situation in a selenium deficient patient even further, and increase the likelihood of radiation-induced side effects during and after therapy [ 34 , 35 , 39 ].…”
Section: Clinical Studies On Seleniummentioning
confidence: 99%